An Acute Bout of Aquatic Treadmill Exercise Induces Greater Improvements in Endothelial Function and Postexercise Hypotension Than Land Treadmill Exercise: A Crossover Study. (August 2018) - Joubert, Dustin P.; Granados, Jorge Z.; Oliver, Jonathan M.; Noack, Bethany L.; Grandjean, Peter W.; Woodman, Christopher R.; Riechman, Steven E.; Crouse, Stephen F.
Abstract : Objective: The purpose of the study was to compare acute bouts of aquatic treadmill (ATM) and land treadmill (LTM) exercise on flow-mediated dilation, postexercise blood pressure, plasma nitrate/nitrite, and atrial natriuretic peptide in untrained, prehypertensive men. Design: In a counterbalanced, crossover design, 19 untrained, prehypertensive men completed bouts of ATM and LTM on separate days. Flow-mediated dilation was measured pre-exercise and 1-hr postexercise. Blood samples were obtained pre-exercise and immediately postexercise and analyzed for plasma nitrate/nitrite and atrial natriuretic peptide. A magnitude-based inference approach to inference was used for statistical analysis. Results: A possible clinically beneficial increase in flow-mediated dilation (1.2%, 90% confidence interval = −0.07% to 2.5%) was observed 1 hr after ATM. In contrast, a possible clinically harmful decrease in flow-mediated dilation (−1.3%, 90% confidence interval = −2.7% to 0.2%) was observed 1 hr after LTM. The magnitude of the postexercise systolic blood pressure reduction was greater after ATM (−4.9, SD = 2.9 mm Hg) than LTM (−2.6, SD = 2.5 mm Hg). Atrial natriuretic peptide increased 34.3 (SD = 47.0%) after ATM and decreased −9.0 (SD = 40.0%) after LTM. Conclusions: An acute bout of ATM induced a more favorable endothelial response and greater postexercise hypotensive response than LTM. These changes were associated with increased atrial natriuretic peptide levels after ATM.